EFFECT OF CLAY MINERALS, CALCITE, AND ORGANIC MATTER ON ADSORPTION AND DESORPTION OF CADMIUM AND LEAD - Ashrf M. Shref; Abdul Baqi D.S. Al Maamouri; Mazin F. Khudhair; Firas W. Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A Factorial experiment of CRD was conducted, to study and evaluate the effectiveness of Calcite, Bentonite, and Kaolinite minerals, as well as organic matter, on adsorption and desorption of Pb and Cd. Bentonite and kaolinite clay minerals were treated by adding of 20 % calcite and 5 % organic matter of the weight of the mineral, so that the final weight became 100 g per treatment. Treatments were incubated for 180 days after that, and treated with five concentrations of Pb and Cd, (0, 10, 20, 30, 40, and 50 μg ml-1) as PbCl2 and CdSo4 respectively, The results showed the superiority of bentonite mineral over kaolinite in the maximum adsorption Xm and binding energy K by 137, 312.5, 20, and 193.5 % for Pb and Cd respectively. In the case of calcite mineral with both minerals, an increase in the binding energy and the greater adsorption were observed in the case of Cd and a decrease in the case of Pb with bentonite. In case of presence of organic matter with kaolinite, the maximum adsorption Xm for cadmium increased, as it was 204.08 μg g-1, while in the case of bentonite with organic matter it was 111.1 μg g-1. In the case of Pb, it reached 93.46 and 208.3 μg gm-1 for both minerals betonies and kaolinite, respectively. Regarding collective release, the results showed that the order of the treatment for the released Cd was as follows: M2 + O.M + C = M2 +O.M < M2 < M2 +C < M1 + C < M1 < M1 +O.M + C < M1 + O.M In the case of released Pb, the order of treatment was as follows: M1 < M1 + C = M1 + O.M < M1 + O.M + C < M2 + O.M + C < M2 + C < M2 + O.M < M2.